ANALYSIS OF CORRELATION AND SPECTRAL CHARACTERISTICS OF FRACTAL COMB-STRUCTURED SIGNALS - Politanskyi, Ruslan; Veryga, Andrij (Informatyka, Automatyka, Pomiary w Gospodarce i Ochronie Środowiska, 2016)
The paper presents theoretical and experimental investigations of the spectra of fractal comb-structured signals for different values of their coefficient of generation, as well as analyzes autocorrelation characteristics and phase portraits depending on the coefficient of generation. It is established that signal base increases with increasing fractal order and with decreasing coefficient of generation.